PCL/PHBV Microparticles as Innovative Carriers for Oral Controlled Release of Manidipine Dihydrochloride - Fernanda Malaquias Barboza; Willian Moreira Machado; Luiz Renato Olchanheski Junior; Josiane Padilha de Paula; Sônia Faria Zawadzki; Daniel Fernandes; Paulo Vitor Farago (The Scientific World Journal)
Microparticles of poly(ε-caprolactone) (PCL) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) containing manidipine dihydrochloride (MAN) were successfully prepared by the simple emulsion/solvent evaporation method. All formulations showed loading efficiency rates greater than 80% and average particle size less than 8 μm. Formulations had spherical shape with smooth and porous surface for PCL and PHBV, respectively. According to Fourier-transform infrared spectroscopy, initial components were not chemically modified during microencapsulation. X-ray diffraction patterns and differential scanning calorimetry demonstrated that this process led to drug amorphization. In vitro dissolution studies showed that all microparticles prolonged MAN release, mainly which one obtained using PCL that contained 5% of drug loaded (PCL-M5). Animal studies demonstrated that formulation PCL-M5 was able to keep the variation of mean arterial pressure after phenylephrine administration up to 24 hours. These data confirmed the sustained antihypertensive effect of the investigated microparticles. Results provided an experimental basis for using formulation PCL-M5 as a feasible carrier for oral controlled release of MAN intended for treating high blood pressure.